Correlações Estratigráficas Conflitantes no Limite Permo-Triássico no Sul da Bacia do Paraná: O Contato Entre Duas Seqüências e Implicações na Configuração Espacial do Aqüífero Guarani - SOARES, ANA PAULA; SOARES, PAULO CÉSAR; HOLZ, MICHAEL (Pesquisas em Geociências, 2008)
The stratigraphic register of the Guarani aquifer system in the Parana basin involves deposits of the Triassic to the Cretaceous. The register in the south region differs from the other areas of the basin, causing confusion in the stratigraphic conception of the Pirambóia Formation. This formation is correlated with paleozoics deposits whose register is only found in the south region of the basin. The correlation that intends for these units has implications in the space configuration and distribution of the aquifer. The space relationships of this record are reinterpreted. The Rio do Rasto Formation, of late Permian age record alluvial plain system, in a progressive semiarid environment, including dune fields; in the southern part of the basin these dune field are extensive and is represented by thick record, covered again by extensive fluvial deposits of the Sanga do Cabral Fm at the PT boundary. The unconformity above records a generalized uplift, associated to the Gondwanides orogeny and to climatic changes, accompanied by progressive supply and sin-sedimentary deformation. Above the unconformity, aeolian and fluvial deposits of the Mesozoic sequence present division organized in 3 blocks: West, Central and East. Three depositional cycles were identified. The first, unconformable over Permian rocks, occurs only in the Central Block, with fluvial and lacustrine deposits filling small rifts (Santa Maria and Caturrita fms). The second cycle extends over the whole basin with fluvial deposits and humid aeolian (formations Guará and Pirambóia); the fluvial and aeolian Guará Fm lies unconformable over Sanga do Cabral Fm in the West Block. In the East Block the aeolian and fluvial unit identified as Pirambóia Fm correlative; it occurs unconformable over the Rio do Rasto Fm, omitting the Sanga do Cabral Fm and the rocks of the first cycle. The third cycle system tract records super arid dune fields of the Botucatu Formation. The Late Permian aeolian facies of the Sanga do Cabral Fm, previously called by some authors as the Pirambóia Fm, doesn't present interfingers and doesn't constitute a hydrostratigraphic unit connected to the Guarani System.